Comparative Proteomics Reveals Strain-Specific β-TrCP Degradation via Rotavirus NSP1 Hijacking a Host Cullin-3-Rbx1 Complex. - Siyuan Ding; Nancie Mooney; Bin Li; Marcus R Kelly; Ningguo Feng; Alexander V Loktev; Adrish Sen; John T Patton; Peter K Jackson; Harry B Greenberg (PLoS Pathogens)
Rotaviruses (RVs) are the leading cause of severe gastroenteritis in young children, accounting for half a million deaths annually worldwide. RV encodes non-structural protein 1 (NSP1), a well-characterized interferon (IFN) antagonist, which facilitates virus replication by mediating the degradation of host antiviral factors including IRF3 and β-TrCP. Here, we utilized six human and animal RV NSP1s as baits and performed tandem-affinity purification coupled with high-resolution mass spectrometry to comprehensively characterize NSP1-host protein interaction network. Multiple Cullin-RING ubiquitin ligase (CRL) complexes were identified. Importantly, inhibition of cullin-3 (Cul3) or RING-box protein 1 (Rbx1), by siRNA silencing or chemical perturbation, significantly impairs strain-specific NSP1-mediated β-TrCP degradation. Mechanistically, we demonstrate that NSP1 localizes to the Golgi with the host Cul3-Rbx1 CRL complex, which targets β-TrCP and NSP1 for co-destruction at the proteasome. Our study uncovers a novel mechanism that RV employs to promote β-TrCP turnover and provides molecular insights into virus-mediated innate immunity inhibition.